Violent International Relations. (September 2020) - Van Milders, Lucas; Toros, Harmonie
Can International Relations (IR) be studied without reproducing its violence? This is the central question of this article. To investigate this, the first step is to expose the violence that we argue remains at the heart of our discipline. The article thus begins by exploring the disciplinary practices firmly grounded in relations of coloniality that plague disciplines more broadly and IR in particular. An analysis of IR's epistemic violence is followed by an autoethnographic exploration of IR's violent practices, specifically the violent practices in which one of the article's authors knowingly and unknowingly engaged in as part of an impact-related trip to the international compound of Mogadishu International Airport in Somalia. Here the article lays bare how increasing demands on IR scholars to become 'international experts' having impact on the policy world is pushing them more and more into spaces governed by colonial violence they are unable to escape. The final section of this article puts forward a tentative path toward a less violent IR that advocates almost insignificant acts of subversion in our disciplinary approach and practices aimed at exposing and challenging this epistemic and structural violence. The article concludes that IR does not need to be abandoned, but rather, by taking on a position of discomfort, needs to acknowledge its violence and attempt to mitigate it – one almost insignificant step at a time.